Implementasi Fungsi Pengawasan BPD Terhadap Akuntabilitas Penggunaan Keuangan Desa di Desa Kembang Mekar Sari Kabupaten Indragiri Hilir - Haironi; Jamri; Kms. Novyar Satriawan Fikri (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aims to determine the implementation of the Village Consultative Body (BPD)'s oversight function regarding accountability for village financial use in Kembang Mekar Sari Village, Indragiri Hilir Regency, based on Law Number 6 of 2014 concerning Villages. The factors influencing the suboptimal implementation of the BPD's oversight function, as well as the legal and governance implications of this suboptimal oversight function, are discussed. This study employed a sociological legal research approach with an empirical approach. The research location was Kembang Mekar Sari Village, Indragiri Hilir Regency. The data used consisted of primary data obtained through interviews with the BPD Chairperson, Village Head, and community leaders, as well as secondary data obtained from laws and regulations, books, and scientific journals related to village governance and village financial management. Data analysis was conducted qualitatively using descriptive analytical methods. The results indicate that the implementation of the BPD's oversight function regarding village financial use in Kembang Mekar Sari Village has been carried out through BPD involvement in village budget (APBDes) discussions, supervision of village development implementation, and evaluation of village budget accountability reports. However, its implementation has not been optimal because supervision remains administrative and formal. Factors contributing to this lack of oversight include the limited quality of human resources within the Village Consultative Body (BPD), minimal training and development, low community participation, social and cultural kinship within the village, and a lack of transparency in the use of village finances. This suboptimal oversight has legal and governance implications for village governance, including increased potential for maladministration and budget misuse, weak implementation of transparency and accountability principles, and declining public trust in the village government.